LANGUAGE ATTITUDE OF INDONESIAN FOOTBALL FANS ON INSTAGRAM - Setiyadi, Dwi Setiyadi; Larastika Suryanto, puput jianggimahastu; Utami, Irine Budi (Universitas 17 Agustus 1945 Semarang, 2021)
The football phenomenon in Indonesia always becomes a hot issue. Indonesians football fans play a big role in the popularity of their football team. The use of social media like Instagram gives them a chance to show their loyalty to their favorite team. The language attitude of Indonesia football fans on Instagram has become an interesting topic to be discussed. This research is aimed to identify the meaning of the language used by Indonesian football fans on Instagram. The discussion of the research includes; (1) Term of Indonesia football used, (2) Social-culture context on Instagram, (3) The meaning of language attitude by Indonesian football. This research used descriptive qualitative as the approach based on the data documentation on Instagram comments done by the researcher. The analysis of the comment by Indonesian football fans is limited on the @liga1match account post. The data is analyzed through three activities; data reduction, data display, and verification. This research found, (1)There are three types of football terms. (2) There are four aspects of social culture. (3) There are football fans with positive & negative language attitudes. The finding of the research can help to gain the conclusion that this condition is due to the factor of solidarity (supporting the club) and rivalry.Â Keywords: Language attitude, Indonesian football fans, sociolinguistic